O atentado das Olimpíadas de Munique como marco de segurança no esporte - Hakim, Sarah (2022)
On August 26, 1972, the Munich Olympics began, with the presence of 121 delegations and more than seven thousand athletes. The host country, in order to ward off the image of the Nazi regime, conceived an event unrelated to policing and ostensible forces, using a very small security budget compared to the subsequent Olympics. On September 5, 1972, Munich awoke to the sounds of gunfire, sirens, and military trucks. The international media reported an uncertain situation about the athletes taken hostage, who later turned out to be Israeli. The fragility of security, exacerbated by the poor conduct of negotiations, made the hostages fatal victims: Ze'ev Friedman, Eliezer Halfin, David Berger and Yaakov Springe, Yossef Gutfreund, Kehat Shorr, Mark Slavin, Amitzur Shapira and Andrei Spitzer. Although terrorism has always punctuated history, its substantial growth took place in the 70s, with the action of the Red Brigades, in Italy, Baader-Meinhof, in West Germany, IRA, in Northern Ireland, ETA, in Spain and Arab-Israeli conflicts. Of the many terrorist actions, two gain special attention, as they determined changes not only in the context of the security of sporting events, but also for the regulation and prevention of terrorist acts they gave rise to, namely: the hijacking of flight 571, from Brussels to Tel Aviv, on May 8, 1972, and the here treated Massacre at the 1972 Munich Olympics. The attack at the Olympics shocked the world, not least because they were the first games broadcast in real time to millions of people from different parts of the planet. 10 Due to the Olympic tragedy, on December 18, 1972, three months after the Munich bombing, therefore, the United Nations General Assembly approved Resolution 3034 (XXVII) which created the Special Committee on Terrorism, called the Committee of 35, with activity between 1973 and 1979, whose institution denotes the need for specific legislation, giving rise to the supervening regulation to repress terrorism. The scope and legal limits of responsibilities in sporting mega-events are explored as a means of observing the legal order of security and fundamental human rights and values. This work narrates one of the saddest pages of the Olympics and its repercussions in the legal sphere, including the responsibility of the IOC and the host State, which after almost 50 years remain reticent about assuming their obligations to the athletes' families, the history of It's the world